2015
DOI: 10.5901/mjss.2015.v6n5s1p494
|View full text |Cite
|
Sign up to set email alerts
|

Study of Life Satisfaction and Happiness among Male Patients of Diabetes: Insulin Vs Non Insulin

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Approximately 35% of people with diabetes have high/very high stress levels, while depression has been observed in 38% to 56.8% of the diabetic population [ 8 , 9 , 12 ]. In addition, studies to estimate life satisfaction levels, QoL, and psychological wellbeing in people with diabetes have also been conducted across the country [ 29 , 30 , 31 , 32 ]. A moderate level of satisfaction was reported in 54.4% of the population with diabetes, and 65% were not sure whether they were happy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 35% of people with diabetes have high/very high stress levels, while depression has been observed in 38% to 56.8% of the diabetic population [ 8 , 9 , 12 ]. In addition, studies to estimate life satisfaction levels, QoL, and psychological wellbeing in people with diabetes have also been conducted across the country [ 29 , 30 , 31 , 32 ]. A moderate level of satisfaction was reported in 54.4% of the population with diabetes, and 65% were not sure whether they were happy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A moderate level of satisfaction was reported in 54.4% of the population with diabetes, and 65% were not sure whether they were happy [ 30 ]. Insulin users were found to be less happy than noninsulin users [ 29 ]. Regular physical activity was associated with psychological wellbeing [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that level of life satisfaction is a good predictor of quality of life in individual with diabetes mellitus. [16,17,18], although this was reported to be majorly influenced by community involvement in management of elderly with diabetes mellitus [19] Different researchers have shown that various types of social support are beneficial for health. Good Social support increases quality of life and sense of quality of life in struggling with chronic illness [20].…”
Section: Worldmentioning
confidence: 99%